STRUKTUR MODAL PADA PERBANKAN SYARIAH - Nursyamsu Nursyamsu (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
An Islamic financial institutions so it should be emphasized that mechanisms and financial and capital structure in accordance with the principles of Sharia, which is not only focused only on achieving maximum profit alone but how to manage the institution for the welfare and convenience of the ummah. In this case the profit is not only to kepantingan owners or founders, but also very important for the development of Islamic banks. Islamic bank profits mainly derived from the difference between the return on investment of funds and the costs incurred during a specific period. In order to obtain optimal results, Islamic banks are required to manage funds effectively and efficiently, both on funds collected from the public, as well as capital funds owner / founder of Islamic banks as well as on the use or cultivation of these funds. Based on the description above in the discussion this time will be described on the capital structure of Islamic financial institutions. And some of the differences between the fund management pattern of conventional banks with Islamic banks, in the management of funds of Islamic banks as well. Can meet the minimum level of liquidity, profitability and solvency were good.